The Influence of Social Safety Capital and Safety Motivation on Safety Citizenship Behavior with Safety Leadership as a Moderator among Operations Employees at PT Kereta Api Indonesia (Persero) - Iqbal T Iskandar; Neuneung Ratna Hayati (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to examine the influence of Social Safety Capital (SSC) and Safety Motivation (SM) on Safety Citizenship Behavior (SCB) with Safety Leadership (SL) as a moderating variable among operational employees of PT Kereta Api Indonesia (Persero). This quantitative study surveyed 450 respondents. Structural Equation Modeling (SEM) analysis showed significant positive effects of SSC and SM on SCB, with SL strengthening the relationship between SM and SCB. The findings contribute academically to human resource management and offer practical recommendations for safety management at PT KAI that indicate that both Social Safety Capital and Safety Motivation positively affect Safety Citizenship Behavior. Furthermore, Safety Leadership activities moderate the relationship between these variables and employees' safety behavior, significantly enhancing workplace safety. safety citizenship behavior, social safety capital, safety leadership, safety motivation.enter